Profit Analysis of Small Holder Dairy Cattle Farm on Group and Individual System in Banyumas Regency - Mastuti, Sri; Widiyanti, Rahayu (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2002)
This research is aimed to study production, technical and the profit of group and individual system on smallholder dairy cattle farm. The research has been conducted in Banyumas Regency. Data collection was done by surveying about 80 farmers, Unit Output Price Cobb-Douglas Profit Function estimation employed Ordinary Leas Square (OLS) method. The different of variable from the result of profit estimation. Profit function analysis on group system showed that manpower pay, animal age, lactation period, lactation month and farmer education have a significant influence on the profit. Whereas, on individual system influence of manpower pay, animal age and lactation month were significant on the profit. Dummy variable showed that group system has more profit than individual system, it was because on group system; (1) has cheaper price on forage and concentrate cost, (2) has higher average of production result, and (3) has higher price ofÂ milk per unit. (Animal Production 4(2): 94-100 (2002)Â Key words : Profit, Group and Individual System